Uso de la tecnología led para el alumbrado público y domiciliario de la Provincia de Santa Elena - Ricardo Borbor, Agustín Alfredo (2019)
LED technology is now afloat, so it is currently intended to replace traditional lamps (incandescent or fluorescent) for the reason of their higher power consumption, making the LEDs (light emitting diode) pass to the foreground since its power consumption is approximately 40% less than traditional lamps, LEDs or light emitting diodes have always been used in the world of technology as light indicators, since they are semiconductor devices that they emit light when an electric current flows through it. LED technology has taken its most recent step with the white light LED’s that are the ones that can replace the light bulbs, mainly because they consume less electrical energy which focuses on environmental care. This project gives a historical review of led technology. Its operating principle and what are its advantages when applied to any human need and its disadvantages, which in comparison with the advantages are minimal, are also presented here.